Successful thrombolytic therapy with recombinant tissue-type plasminogen activator for massive pulmonary embolism -A case report- - Min Soo Kim; Kye-Min Kim; Seung-Hoon Woo; Yun Hee Lim; Jun Heum Yon; Seung-Gyu Jeon (Korean Journal of Anesthesiology, 2010)
Massive pulmonary embolism is associated with significant perioperative morbidity and mortality. We report here on a case of a 69-year-old man who suffered a massive pulmonary embolism with pulseless electrical activity during knee arthroscopic surgery. After a diagnosis was made by performing transthoracic echocardiography, the patient was treated with recombinant tissue-type plasminogen activator. The patient was transferred to the intensive care unit after his hemodynamic status improved. The patient went on to make a full cardiopulmonary recovery without any complications.